Effect of online solution-focused counseling on the sexual quality of life of women with a history of breast cancer: a clinical trial - Mahshid Bokaie; Nafiseh Sadat Hejazi; Mirsaeed Jafari; Masoud Shabani (BMC Women's Health, 2023)
Abstract Background Breast cancer, as the most prevalent malignancy among women globally and in Iran, affects important aspects of the lives of the survivors of this condition, especially the quality of sexual life. Solution-focused brief therapy is one of the therapeutic counseling approaches used in various fields, including sexual function problems. In recent years, online and internet-mediated counseling methods have received more attention. Objective This study investigated the effect of online counseling based on a solution-focused approach in improving the sexual quality of life (SQL) of women with breast cancer. Materials & methods In this clinical trial, the research population consisted of women with a history of breast cancer with a recorded file in Shahid Ramazanzadeh Radiation Oncology Center in Yazd and at least 6 months had elapsed since the end of their treatment. After selecting 80 samples based on the random numbers table, they were assigned into two groups of 40, i.e., active control and intervention, using random allocation software. Participants in the intervention group were given online counseling through the Skyroom space with a solution-focused approach. Eight weekly sessions were held each lasting 60–90 min. The active control group received an educational file to improve the SQL. All participants in two groups completed the SQL questionnaire at the beginning of the study, at the end of the study, and 1 month after the study. Data were analyzed with SPSS18 using descriptive and inferential statistics. Results Finally, the data of 33 participants in the intervention group and 32 participants in the active control group were analyzed. The mean score of the SQL in the intervention group increased from 68.57 ± 18.63 before the intervention to 78.84 ± 12.7 immediately after the intervention (P = 0.015), and to 79.60 ± 19.88 1 month after the intervention (P = 0.012). The mean score of the SQL in the active control group increased from 64.45 ± 22.76 before the intervention to 67.20 ± 20.29 immediately after the intervention (P = 0.33), and to 68.70 ± 20.76 1 month after the intervention (P = 0.62). The difference in the mean score of the SQL before and after the intervention between the two groups was statistically significant (P = 0.007). Conclusion It seems that the use of counseling with a solution-focused approach in women with a history of breast cancer improves the SQL. Thus, considering the effectiveness of this type of training, it is recommended that this method be used as a sexual health counseling method in medical centers. Trial registration This clinical trial is registered in Iranian registry center of clinical trials (IRCT) by registration code of IRCT20201221049784N1 in 06/03/2021.